PENGARUH PEMBERIAN PAKAN ALTERNATIF LIMBAH IKAN ASIN DAN TEPUNG KEDELAI TERHADAP PERTUMBUHAN IKAN LELE DUMBO (Clarias gariepinus) - andri jaya kesuma (Politeknik Pertanian Negeri Kupang, 2019)
The production sector of Clarias gariepinus every year has increased. One obstacle to the cultivation of Clarias gariepinus is the high cost of commercial feed. This study aims to determine the effect of alternative feeding of salted fish waste and soy flour to the growth of Clarias gariepinus. This research was conducted in December 2018 - January 2019. The parameters observed in this study were the length and weight of Clarias gariepinus. The study was conducted using the Rancangan Acak Lengkap (RAL) method using 6 treatments, one of which was as a control and was repeated three times. The results of this study indicate the effect of alternative feeding on the growth of Clarias gariepinus. The best feed was in P2 treatment with a concentration of 75% salted fish meal flour and 25% soy flour, with an absolute length of 5.33 cm, weight of 7.66 grams and the lowest conversion value was 141.